Polymorphic populations of Dactylorhiza incarnata s.l. (Orchidaceae) on the Baltic island of Gotland: morphology, habitat preference and genetic differentiation - Hedrén, Mikael (Oxford University Press, 2009)
BACKGROUND AND AIMS: Organisms may be polymorphic within natural populations, but often the significance and genetic background to such polymorphism is not known. To understand the colour polymorphism expressed in the diploid marsh-orchids Dactylorhiza incarnata, morphological, habitat and genetic differentiation was studied in mixed populations on the island of Gotland, supplemented with genetic marker data from adjacent areas. METHODS: A total of 398 accessions was investigated for plastid haplotype and three nuclear microsatellites. Morphometric data and vegetation data were obtained from a subset of 104 plants. KEY RESULTS: No clear pattern of habitat differentiation was found among the colour morphs. Within sites, the yellow-flowered morph (ochroleuca) was slightly larger than the others in some flower characters, whereas the purple-flowered morph with spotted leaves (cruenta) was on average smaller. However, populations of the same colour morph differed considerably between sites, and there was also considerable overlap between morphs. Morphs were often genetically differentiated but imperfectly separated within sites. Most populations were characterized by significant levels of inbreeding. The ochroleuca morph constitutes a coherent, highly homozygous sublineage, although introgression from purple-flowered morphs occurs at some sites. The cruenta morph was genetically variable, although Gotland populations formed a coherent group. Purple-flowered plants with unspotted leaves (incarnata in the strict sense) were even more variable and spanned the entire genetic diversity seen in the other morphs. CONCLUSIONS: Colour polymorphism in D. incarnata is maintained by inbreeding, but possibly also by other ecological factors. The yellow-flowered morph may best be recognized as a variety of D. incarnata, var. ochroleuca, and the lack of anthocyanins is probably due to a particular recessive allele in homozygous form. Presence of spotted leaves is an uncertain taxonomic character, and genetic differentiation within D. incarnata would be better described by other morphological characters such as leaf shape and stature and size and shape of lip and spur.